PENGARUH TERAPI KOMBINASI RELAKSASI TERHADAP TINGKAT KECEMASAN PASIEN HEMODIALISA - Ariwijaya, Rama; Fitri, Eka Yulia; Adhisty, Karolin (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
Hemodialysis is the process of removing metabolic waste from other toxic substances through a semipermeable membrane as a separator between blood and dialysate fluid which is deliberately made in a dializer. Management of hemodialysis, can cause pain in the fistula puncture area, it can cause anxiety in patients. Furthermore, the length of the hemodialysis process, the threat of death, changes in self-concept, dependence on others, difficulties in maintaining work, financially, changing roles and changing social interactions can also be a cause of the emergence of psychological effects namely anxiety in hemodialysis patients. This study aims to determine the effect of relaxation combination therapy on the anxiety level of hemodialysis patients. This research is a quantitative quasi experimental study using a pretest-posttest control group design. This research was conducted at Palembang Pusri Hospital on 40 patients based on purposive sampling technique. The results showed there was a significant influence between anxiety levels on the administration of relaxation combination therapy interventions by showing that the anxiety level of the intervention group was dominated by mild anxiety at posttest, and in the control group dominated by moderate anxiety at posttest. Data analysis using the mann-whitney test showed that there were significant differences between the anxiety levels of hemodialysis patients before and after relaxation combination therapy with p value = 0.013. This study proves that combined relaxation therapy has a significant effect in reducing anxiety levels in patients with CKD undergoing hemodialysis and can be used as nursing interventions.